Naturgeografi og historisk regionalitet - Grandjean, Johnny G.G. (Hikuin, 2008)
Physical geography and historical regionality By Johnny Grandjean Gøgsig Jakobsen Physical geography is the natural starting-point for studies within the conglomerate discipline of historical geography. Even though the hardcore naturaldeterministic ideas of nineteenth-century historical geographers have long been abandoned, it would be folly to ignore the importance of the physical surroundings for the people living in them. Certainly, the author of the present article supports the concept of a historical-geographical possibilism, as introduced by the French scholar Lucien Febvre, where physical geography is believed to have set the overall frame within which people through history have chosen various creative ways of utilizing the possibilities. The need for keeping the physical geography in mind is even more obvious when studying regional variations, as in this present case of Viking-Age and medieval Denmark. The article gives a short presentation of Danish and Scanian studies, in which historical regionality and physical geography have been analysed and linked. Historical geography as such has in Denmark experienced a series of ups-and-downs, and even though we still await a continuation of the numerous interdisciplinary, state-funded initiatives of the 1990s dealing with various aspects of the historical, cultural landscape, a number of individually based studies by young scholars in recent years within the boundaries of the field of historical-geographical research, often using new technology such as GIS, do bring hope for the future. The final part of the article seeks to provide a physical-geographical regionalisation of medieval Denmark (including Schleswig, Scania, Halland and Blekinge) primarily based on variations in soil and terrain, to the extent that these factors are likely to have played a role for the medieval inhabitants. The classification has suggested eight such physical-geographical regions, and by comparing these regions with the regions identified in the articles below, we may get a better foundation for interpreting the possible reasons for any intra-national, cultural variations within medieval Denmark – or at least be able to judge whether these were based on physical-geographical differences or not.